Embedded soliton dynamics in the asymmetric array of Josephson junctions - Starodub Ivan О.; Zolotaryuk, Yaroslav (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The dc-biased annular array of three-junction asymmetric superconducting quantum interference devices (SQUIDs) is investigated. The existence of embedded solitons (solitons that exist despite the resonance with the linear waves) is demonstrated both in the unbiased Hamiltonian limit and in the dc-biased and damped case on the current-voltage characteristics (CVCs) of the array. The existence diagram on the parameter plane is constructed. The signatures of the embedded solitons manifest themselves as inaccessible voltage intervals on the CVCs. The upper boundary of these intervals is proportional to the embedded soliton velocity.